Dynamics of soybean rust epidemics in sequential plantings of soybean cultivars in Nigeria - Twizeyimana, M.; Ojiambo, P.; Hartman, G.L.; Bandyopadhyay, Ranajit (Scientific Societies, 2011)
Soybean rust, caused by Phakopsora pachyrhizi, is an important foliar disease of soybean. Disease severity is dependent on several environmental factors, although the precise nature of most of these factors under field conditions is not known. To help understand the environmental factors that affect disease development, soybean rust epidemics were studied in Nigeria by sequentially planting an early-maturing, highly susceptible cultivar, TGx 1485-1D, and a late-maturing, moderately susceptible cultivar, TGx 1448-2E, at 30- to 45-day intervals from August 2004 to September 2006. Within each planting date, disease onset occurred earlier on TGx 1485-1D than on TGx 1448-2E, and rust onset was at least 20 days earlier on soybean planted between August and October than on soybean planted between November and April. The logistic model provided a better description of the temporal increase in rust severity than the Gompertz model. Based on the logistic model, the highest absolute rates of disease increase were observed on soybean planted in September 2006 and October 2004 for TGx 1485-1D and TGx 1448-2E, respectively. Disease severity as measured by the relative area under disease progress curve (RAUDPC) was significantly (P < 0.05) negatively correlated with evaporation (r = –0.73), solar radiation (r = –0.59), and temperature (r = –0.64) but positively correlated with urediniospore concentration (r = 0.58). Planting date and soybean cultivar significantly (P < 0.05) affected disease severity, with severity being higher on soybean crops planted during the wet season than those planted in the dry season. Within the wet season, planting in May and July resulted in a significantly (P < 0.05) lower RAUDPC than planting between August and October. Yields were significantly (P < 0.001) related to RAUDPC during the wet season, whereby an increase in RAUDPC resulted in a linear decrease in yield. This study suggests that selection of planting date could be a useful cultural practice for reducing soybean rust.